Carreira dos jovens executivos: competências em destaque para a posição de gerência em seis organizações nacionais de grande porte em diferentes segmentos - Dreifus, Bibiana Balen Zereu (2010)
The main objective of this study is to verify what the competences are common in six companies that were analyzed and the ones highlighted in young men/women managers, who are from 24 to 35 years old, factor that facilitates the contruction of the growing of the professional path. This is a qualitative, exploratory, descriptive and documental research. Data were collected through bibliographical sources, as well as a documental research that was carried out in a multinational consulting firm whose headquarters is in São Paulo. The competences that were highlighted were: high motivation (passion for what you do) in three companies; focus on results that the company would want the manager to achieve, in two; and ability to perform activities, in just one. We concluded that companies search for managers that have those traits: dedication, boldness, criativity, entrepreneurship, trading facility and the ones that focus on results. We also verified that those professionals, besides having graduation, they should concentrate on their personal development, looking for qualification on the former competences.